Visions of life: Resettlement expectations of refugees in Cairo - Perera, Shashikala Visuddhi (AUC Knowledge Fountain, 2019)
This study looked into how refugees in Cairo experience their transition while waiting to be resettled and how and to what extent those experiences shape their expectations of life in the resettlement country. It was conducted among a cohort of Sudanese refugees in the resettlement pipeline living in Cairo using the qualitative research method of phenomenological approach chosen to capture the common elements that individuals living a particular shared experience had with each other. This study found that refugees' expectations are primarily based on rights and liberties that have been denied to them in the land of their birth and previous residence as well as their current site of exile; their expectations correspond to the vast gamut of rights linked to formal citizenship as a status in a political community. Additionally, it also revealed that expectations are generated by the social context in the current site of exile; expectations are engendered by others' reported experiences; and expectations are based on what refugee participants believe to be the norm, not necessarily the reality. During interactions with the study cohort, it was observed that research participants were adhering to a narrative style that exclusively highlighted their vulnerabilities at the current cite of exile, a version that would essentially elicit the attention of the organizations that work with them. This study reiterates that durable solutions should be driven by the true potential and possibility of establishing a meaningful alternative to the broken State-citizenship-territory link that the refugees seek to regain in their sites of asylum and exile. Only then would refugees be able to assert themselves as veritable members of the political community they inhabit and lead meaningful lives that create fertile ground for self-actualization.